The Semantic Structure of narrative discourse in the novel " The Alley of Mudaq " by Naguib Mahfouz - Abdalla, Laila Othman (Arab Journal for Sciences and Research Publishing, 2019)
Understanding the textual structure of the narrative construct in novels is essential in order to explore the aesthetics of fiction writing, which is also a basic factor for reading and criticism in its interpretation and hermeneutic aspects. Accordingly, this study aims to uncover the underlying principles of the narrative structure in the novel ‘The Alleys of Mudaqq’ from the perspective of viewpoint, style, description, rhetoric and language as well as the functions served by the aforementioned discourse modules semantically, formally or pragmatically depending on the semiotic approach. One of the main motives behind this study is the importance of the semantic structure in semiological studies and is considered an important aspect of discourse analysis of narrative text. Even though it goes beyond its role as analyzing the intrinsic and extrinsic meanings of discourse to occasionally serve as description and sometimes as symbolism and at other times in the form of artistic imagery. One of the consequences of semiotics in fiction analysis is that it views fiction as a narrative structure, i. e. , a larger network of relations that underlie the superstructure of a text. Thus, the approach which the semiotic analysis of the narrative discourse suggests is based on linguistic samples that determine the surface and deep structure of the narrative path. Moreover, the narrative system in ‘The Alleys of Mudaqq’ is an objective correlative the framework of which is related to an invitation to the high values and ethics of the humans, i. e. , the value of humans is not measured by the skills or the appearance he/she possesses, rather a human being’s ambitions should be built upon the skills and faculties he/she has and what he/she can actually perform.